Development of Heterocyclic Multicomponent Reactions through Guided Exploration: Direct, Reasonable and Unpredictable Processes - Ghashghaei, Ouldouz; Rodríguez, Pau Nadal; Lavilla, Rodolfo (Synlett, 2022)
This Account summarizes the research of the group on the multicomponent reactions arena with fundamental heterocycles as substrates, using mechanistic considerations to hypothesize new processes and to rationalize results. Biomedical applications of the ensuing adducts were also envisaged, which brought about interesting discoveries.1 Introduction and Context2 The Beginnings: Unexplored Heterocyclic Substrates3 Interrupted Processes4 Multiple Multicomponent Reactions: Problem of Selectivity5 Extended Multicomponent Reactions6 Conclusions and Wishes
Keywords: azines; azoles; heterocycles; multicomponent reactions; reaction discovery; reaction mechanism